Economic impact of a potential Free Trade Agreement (FTA) between the European Union and the Commonwealth of the Independent States - Joseph Francois; Miriam Manchin (Center for Social and Economic Research (CASE), 2009)
We evaluate the effects of potential measures to liberalize trade between the EU and the CIS using a computable general equilibrium (CGE) model. We look At the CIS as an aggregate and we also present results for individual CIS countries Our CGE model takes different underlying industry specific market structures and elasticities into account. Furthermore, the model incorporates estimated non-tariff trade barriers to trade in services. The results are compared to a baseline which incorporates recent developments in the trade policy environment, i.e. the phase out of ATC, enlargement of the EU and CIS accessions to the WTO. The analysis takes agricultural liberalization, liberalization in industrial tariffs, and liberalization in services trade as well as trade facilitation measures into account. Chile there is important heterogeneity in the impact of FTAs on individual countries, the results indicate that the CIS as a whole would experience a negative income effect if the FTA would be limited only to trade in goods. This implies that the CIS would most likely to benefit from an FTA with the EU if it would incorporate deeper form of integration not being limited to liberalization of tariffs in goods.
Keywords: F13; F15; 330; CGE; EU-CIS Free Trade Area; Russia; Ukraine; CIS; Freihandelszone; Handelsliberalisierung; Wirtschaftsintegration; CGE-Modelling; Allgemeines Gleichgewicht; EU-Staaten; GUS-Staaten